Protein homeostasis and the chaperone interaction network in Arabidopsis thaliana - Zhao, Rongmin (Henry Stewart Talks, 2012)
Plant cellular protein quality control systems, Arabidopsis regulated protein degradation by the proteasome, Plant stress resistance, Mechanism of action of molecular chaperones, Molecular chaperones in Arabidopsis, Chaperone interaction networks in Arabidopsis